2011
DOI: 10.1094/ats-2011-0126-02-rs
|View full text |Cite
|
Sign up to set email alerts
|

Low-Input Turfgrass Species for the North Central United States

Abstract: Public attention is being increasingly focused on the environmental impact and management costs of turfgrass areas such as lawns for schools, parks, and homes. The objectives of this study were to: (i) identify grass species adapted to low‐input environments (limited water, no fertilizer or pesticides after establishment) in the North Central Region (NCR) of the USA; and (ii) evaluate these species for turfgrass quality under mowed and non‐mowed conditions. Low‐input turf trials of 12 grass species were establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 14 publications
3
62
0
Order By: Relevance
“…L ow‐input sustainable turfgrass species have previously been tested to determine their suitability throughout the North Central Region (NCR) and other parts of the northern United States and Canada (Dernoeden et al, 1994, 1998; Diesburg et al, 1997; Mintenko et al, 2002; Watkins et al, 2011). These and other studies have shown that several species either are well‐adapted to the northern United States (tall fescue [ Festuca arundinacea ], hard fescue [ Festuca trachyphylla ], sheep fescue [ Festuca ovina ], colonial bentgrass [ Agrostis capillaris ], Chewings fescue [ Festuca rubra var.…”
Section: Introductionmentioning
confidence: 99%
“…L ow‐input sustainable turfgrass species have previously been tested to determine their suitability throughout the North Central Region (NCR) and other parts of the northern United States and Canada (Dernoeden et al, 1994, 1998; Diesburg et al, 1997; Mintenko et al, 2002; Watkins et al, 2011). These and other studies have shown that several species either are well‐adapted to the northern United States (tall fescue [ Festuca arundinacea ], hard fescue [ Festuca trachyphylla ], sheep fescue [ Festuca ovina ], colonial bentgrass [ Agrostis capillaris ], Chewings fescue [ Festuca rubra var.…”
Section: Introductionmentioning
confidence: 99%
“…is one of the most popular turfgrass species for home lawns, sports fields and low maintenance area. Watkins et al (2011) investigated 12 turfgrass species managed under low maintenance and found that tall fescue and hard fescue (Festuca brevipila Tracey) had the highest quality during the research period. Because of its wear resistance, deep root system, and drought tolerances, tall fescue can be well-adapted for low maintain area.…”
Section: Introductionmentioning
confidence: 99%
“…Diesburg et al (10) evaluated 12 turfgrass species for use as low‐input turf in the Upper Midwest and determined that when left unmowed, hard fescue was the top‐performing species. Watkins et al (23) determined that under low‐maintenance conditions and at higher mowing heights (5.1 cm and 10.2 cm) sheep and hard fescue performed well in the North Central Region of the United States. It was also noted that sheep and hard fescue performed well throughout the same region in no‐mow situations (23).…”
Section: Need For No‐mow Low‐inputmentioning
confidence: 99%
“…Watkins et al (23) determined that under low‐maintenance conditions and at higher mowing heights (5.1 cm and 10.2 cm) sheep and hard fescue performed well in the North Central Region of the United States. It was also noted that sheep and hard fescue performed well throughout the same region in no‐mow situations (23). Tufted hairgrass (Deschampsia cespitosa [L.] Beauv.)…”
Section: Need For No‐mow Low‐inputmentioning
confidence: 99%